Respuestas

2013-05-15T16:51:01+02:00

3(0,2x-1)+1,2=0,5+x

3*(0.2x-1)+1.2=0.5+x

0.6x - 3 + 1.2 = 0.5 + x

-3 + 1.2 - 0.5 = x -0.6x

-2.3 = 0.4x

x = -2.3/0.4

x = -5.75

por cierto en forma de fraccion seria: x = - 115/2

 

0,33333x (periodico) - 1/2=1/5 (x+1/3)

(1/3)x -1/2 = (1/5)*(x+1/3)

x/3 -1/2 = x/5 + 1/15

x/3 - x/5 = 1/15 + 1/2

2x/15 = (2 + 15) / (2*15)

2x = 17 / 2

x = 17/4 = 4.25

 

 

1/3x-1=2(1/3x+1/5)

supongo que tratas de decir que la ecuacion es la siguiente

(1/3)x-1=2*((1/3)x+1/5)

x/3 -1 = 2x/3 + 2/5

x/3 - 2x/3 = 2/5 + 1

-x/3 = 7/5

x = - 21/5 = - 4.2

 

 

5(0,2222x(periodico)+1/3)+3/2=1/6x

5*(0.222222*x +1/3) + 3/2 = (1/6)*x

5*((2/9)*x + 1/3) +3/2 = (1/6)*x

10x/9 + 5/3 + 3/2 = x/6

10x/9 - x/6 + 5/3 + 3/2 = 0

17x/18 + 19/6 = 0

x = - 57/17 = 3.3529411

 

 

 

Suerte

Profesoy